Numerical analysis for piezoelectric unimorph beam power harvesting Applications - Eziwarman (Curtin University, 2015)
This research investigated energy harvesting of unimorph piezoelectric beams using numerical methods. Electromechanical coupled transformation and non-orthonormalised solution methods were introduced to model the voltage, current and power FRFs. Case studies investigated the contribution of axial and transverse deformation and changing neutral axis of segmented piezoelectric components for different unimorph piezoelectric beam applications. Analysis of beams with varying orientation showed that axial coupling must be accounted for to correctly model the system power.